2012
DOI: 10.1159/000342489
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Risk Factors, Prognosis, and Genetic Polymorphism of the Cyclooxygenase-1 Gene for Aspirin Resistance in Elderly Chinese Patients with Cardiovascular Disease

Abstract: Background: Cardiovascular disease (CVD) is an important cause of mortality in elderly patients worldwide. Aspirin resistance has been well reported in CVD. Objective: The frequency, risk factors, prognosis, and genetic polymorphism of the cyclooxygenase-1 (COX-1) gene for aspirin resistance have not been reported in elderly patients with CVD. We therefore undertook this study to evaluate these associations among elderly Chinese patients with CVD. Methods: Four hundred thirty-one elderly Chinese patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Another study by Fan et al . found that the variant T-allele of COX-1 rs1330344 was significantly associated with AR determined by LTA and thromboelastography platelet mapping assay using AA as a stimulus [ 36 ]. Similar results were also reported using AA-induced LTA combined with ADP-induced LTA to distinguish AR and non-AR [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Fan et al . found that the variant T-allele of COX-1 rs1330344 was significantly associated with AR determined by LTA and thromboelastography platelet mapping assay using AA as a stimulus [ 36 ]. Similar results were also reported using AA-induced LTA combined with ADP-induced LTA to distinguish AR and non-AR [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Still on the PTGS1 gene, Fan et al investigated several polymorphisms of the PTGS1 gene (rs1888943, rs1330344, rs3842787, rs5787, rs5789, and rs5794), but rs1330344 was the only significantly related to AR (p ¼ 0.01; OR ¼ 1.82; 95% CI ¼ 1.13-2.92; allele value) just in LTA þ TEG analysis. 30 Moreover, another case-control study by Chakroun et al investigated the relationship between rs3842787 polymorphism of the PTGS1 gene and AR. Patients with the allele had no statistically significant difference using CEPI-CT (p ¼ 0.1) and uTxB2 (p ¼ 0.43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the variant G allele of PTGS1 rs1330344 has a positive association with aspirin resistance in cardiovascular disease. 38 Some researchers have focused on the PTGS1 gene and the relationship between its polymorphisms and cardiovascular event susceptibility. Zhao et al 27 investigated 5 PTGS1 gene variants (rs5788, rs1330344, rs3842788, rs20417, and rs689466) and found that the rs1330344 AA genotype may decrease susceptibility to ischemic stroke and that the interaction between PTGS1 (rs1330344 and rs3842788) and PTGS2 rs689466 increases susceptibility to small vessel occlusion.…”
Section: Discussionmentioning
confidence: 99%